Novel Trifluoromethyl Pyridine Derivatives Bearing a 1, 3, 4‐Oxadiazole Moiety as Potential Insecticide. Issue 10 (12th March 2018) - Xu, Fangzhou; Wang, Yanyan; Luo, Dexia; Yu, Gang; Wu, Yikun; Dai, Ali; Zhao, Yonghui; Wu, Jian
Abstract: A series of trifluoromethyl pyridine derivatives containing an 1, 3, 4‐oxadiazole moiety was synthesized and characterized by 1 H NMR, 19 F NMR, 13 C NMR, and HR‐MS. The bio‐assay results indicated that some of the synthesized compounds exhibited good insecticidal activity against Mythimna separate and Plutella xylostella . Most of the synthesized compound showed 100% activity against the two pests at 500 mg⋅L −1 ; in practically, the value of median lethal concentration (LC50 ) for some title compounds was much lower than that of commercial chlorpyrifos. Preliminary structure‐activity relationship was also discussed. Abstract : Trifluoromethyl pyridine derivatives with an 1, 3, 4‐oxadiazole moiety was synthesized and bio‐assayed for their insecticidal activity against Mythimna separate and Plutella xylostella . Some of the compound showed 100% activity against the two pests; in practically, partial compounds showed much better activity against Plutella xylostella than that of commercial chlorpyrifos.